General anesthesia versus deep sedation for children undergoing invasive procedures in oncologic clinic. - S. Shah-Hosseini; Z. A. Fang; C. J. Bae; K. A. Harris; R. M. Chiavacci; R. Aplenc; A. F. Reilly; A. E. Kazak; S. D. Cook-Sather (Pediatric Anesthesia and Critical Care Journal, 2018)
Abstract Introduction Several successful general anesthetic and deep sedation techniques have been established for children under- going invasive oncologic procedures. This pilot pro- spective cohort study examined whether general ane- sthesia facilitated lumbar puncture and bone marrow aspiration and improved patient conditions better than sedation in patients with acute lymphocytic leukemia. Materials Nineteen children with newly diagnosed leukemia who required day seven lumbar puncture/bone marrow aspi- rates at the Children's Hospital of Philadelphia were en- rolled. Subjects were initially randomized, but due to falling recruitment, the final nine subjects were allowed to choose treatment arm. Ten patients received sedation and nine received general anesthesia. Intravenous mi- dazolam and fentanyl were administered for sedation. General anesthesia subjects were induced with intrave- nous lidocaine and propofol, and maintained by mask with isoflurane or sevoflurane and N2O in O2. Procedure room entry, procedure start and finish, and discharge readiness times were recorded. Serum cortisol, epineph- rine, and norepinephrine levels were determined. Proce- dural difficulty and parent/child comfort levels were measured using 10 cm visual analog scales. Validated instruments were used to assess anxiety, quality of life, and satisfaction. Results Average preparation time (34.0+21.8 min vs. 11.6+10.2 min, p=0.01) and procedure time (19.4±8.8 min vs. 8.1±5.9 min, p=0.005) were longer for sedation. Onco- logists rated sedation procedures more difficult than ge- neral anesthesia (4.3±4.4 vs. 0.8±0.8, p=0.03). General anesthesia decreased neither recovery time nor time to discharge readiness (25.0±21.1 min vs. 34.1±9.2 min, p=not significant). Neither parental perception of child comfort nor overall satisfaction differed significantly between groups. One failed sedation required conver- sion to general anesthesia. Conclusions General anesthesia improved operative conditions, redu- ced procedure time, and decreased variability in recove- ry time without increasing side effects. General anesthe- sia did not appear to alleviate patient anxiety, improve comfort, or reduce discharge readiness time over seda- tion.